A study of the kinematics of unusually H I‐rich galaxies. Issue 3 (April 2015) - den Heijer, M.; Jözsa, G. I. G.; Kerp, J.; Serra, P.; van der Hulst, Th.; Kauffmann, G.; Wang, J.; Bigiel, F.; Brinchmann, J.; Carton, D.; Cormier, D.; Huang, M.‐L.
Abstract We examine the H I kinematics of the "Bluedisk" ensemble of 48 galaxies selected from the Sloan Digital Sky Survey and observed in H I with the Westerbork Synthesis Radio Telescope. The sample consists of 25 galaxies with a high H I mass fraction and a comparatively large control sample comprising 23 galaxies of comparable stellar mass, stellar mass surface density, redshift, and inclination. By studying the H I velocity fields of these galaxies, we investigate whether there are signatures of ongoing gas accretion: i.e. global asymmetries and indications for warping and kinematical lopsidedness. We find no enhanced kinematical asymmetries between the H I‐rich sample and the control sample galaxies, indicating no significant difference in kinematical signatures such as warping and lopsidedness. Furthermore, we find no difference in position angle and systemic velocity offset with respect to the optical between both sub‐samples. We therefore do not find compelling evidence for enhanced global asymmetry of the H I‐excess galaxies ensemble properties in comparison to the control sample galaxies. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)